GAMBARAN REGULASI EMOSI PADA IBU YANG MEMILIKI ANAK BERKEBUTUHAN KHUSUS - Andini Arzetta Bilbina Pohan; Rina Mirza; Anita Mestika Juandina; Alexsius Gulo; Mawaddah Nasution (Program Studi Bimbingan dan Konseling FKIP UMSU, 2023)
Everyparents wants a child who is born normally, but what if the child is not normal, not only physically but also mentally. So many negative emotions are felt by parents who have children with physical and mental disabilites, it affects to the children growth, especially mothers who are considered as the important figure to take care their children. The purpose of this research is to find out the description of emotional regulation in mothers who have children with physical and mental disabilities. This research uses a qualitative research method with a phenomenological approach. Respondents in this research are 8 mothers with a characteristics, those are 4 mothers who have children with Down syndrome and 4 mothers who have children with Autism. The results showed that mothers who have children with physical and mental disabilities felt negative emotions such as sadness, disappointment, anger, upset, surprised, despair, being hit and wanting to cry. The ways is used by respondents to regulate their emotions are accepting their childs condition, getting closer to God and trying to be patient, praying and spending more time with their child. They are able to regulate their emotions by evaluating and changing emotional reactions, so that they can behave adaptively according to the situation that occurs